Coordination Impairments Are Associated With Falling Among Older Adults. Issue 5 (20th October 2017) - James, Eric G.; Leveille, Suzanne G.; Hausdorff, Jeffrey M.; Barton, Bruce; Cote, Sarah; Karabulut, Murat; Conatser, Phillip; Kennedy, David N.; Tucker, Katherine L.; Al Snih, Soham; Markides, Kyriakos S.; Bean, Jonathan F.
ABSTRACT: Background/Study Context : Approximately one third of older adults over the age of 65, and over 40% of those over 80 years, fall each year, leading to fractures, morbidity, and mortality. Annual direct medical costs due to falls in the United States are approximately 19.2 billion. The identification of new treatable risk factors for falls has the potential to advance their prevention and rehabilitation. Methods : A cross-sectional study of 127 community-dwelling adults aged 67-99 years was conducted. An electronic gait walkway was used to assess gait coordination, measured as the Phase Coordination Index during normal speed walking. A motion capture system was used to assess rhythmic interlimb antiphase ankle coordination, measured as the standard deviation of ankle relative phase. Having fallen in the previous year was self-reported retrospectively. Odds ratios for falling as a function of coordination quartiles were determined using multivariable logistic regression. Results : Adjusting for age, sex, body mass index, number of chronic conditions, Mini-Mental State Examination score, gait speed, and the variability of step length, time, and width, the odds ratios for falling based upon being in the 4th (the poorest) quartiles of gait or ankle coordination were 5.5 (95% confidence interval [CI]: 1.2–24.7) and 8.2 (95% CI: 2.2–31.3), respectively, and 3.7 (95% CI: 1.0–13.8) for the 3rd quartile of gait coordination, compared with the best (the 1st) coordination quartiles. Similar results were found in regression without adjustment for gait characteristics. Conclusion : The results support the hypothesis that impaired gait and rhythmic interlimb ankle coordination are associated with a history of falls in the past year. Prospective longitudinal research is needed to determine the possible direction of causality between falls and impaired coordination.